Delirium como foco de atenção para os enfermeiros de terapia intensiva - Parejo, Lucinéia Stach [UNESP] (2014)
Delirium is a manifestation of acute brain dysfunction which is frequent in critically ill patients and associated with increased morbidity and mortality. In the experience of Intensive Care Units (ICUs), this situation affects many patients during the hospitalization period, and the frequency of events increases as the hospitalization period extends. With this regard, this study aimed at understanding the concepts attributed to Delirium by ICU nurses for preventive, diagnostic and therapeutic approaches in the care for patients showing this diagnosis. It was a qualitative study with a methodological framework based on Content Analysis and conducted in two adult ICUs in public hospitals in São Paulo state - Brazil, one of which was located in inner São Paulo state and the other in the state capital city. Data were collected from April to July 2013 by means of semi-structured interviews in which 18 female nurses whose ages were predominantly between 25 and 30 years and who had worked in the care for critical patients for 1 to 5 years participated. The results in the study originated seven categories according to the following topics: Delirium is confusion, agitation, hallucination and aggressiveness. It has multiple causal circumstances associated with the ICU environment, abstinence from drug and alcohol use, previous psychiatric disease and the use of pharmaceuticals/sedatives. In the topics related to possible prevention strategies, the following emerged: greater contact with one’s family, functional and structural adequacy of the environment and intentionality of communication with the patient. As regards the Delirium diagnosis, nurses reported that behavioral changes define it, and special attention must be paid to non-verbal communication signs. Delirium treatment may take place by mechanical restriction as a therapeutic method and by the use of pharmaceuticals as a means of patient restraint, pointing out verbal communication ...